NEW SCHEMES AHROMATIC STATIC MASS-SPECTROMETERS - Baisanov, O.A.; Доскеев, Г.А.; Spivak-Lavrov, I.F. (Recent Contributions to Physics, 2018)
Here offered and calculated new schemes of the sector mass-spectrometers, in which for focusing on energy are used unusual electrostatic systems, consisting of electrostatic prism and transaxial of the lens.